Effect Of Competency and Career Development on Employee Performance at PT. Indojaya Sukses Makmur in Jakarta - Widhi Wicaksono; Suyatin Suyatin; Eko Cahyadi; Panji Galih Kusumo Adie; Muhammad Andrei Lesmono (Program Doktor Ilmu Manajemen, Universitas Pasundan, Indonesia, 2021)
This study aims to determine the effect of competence and career development on employee performance at PT. Indojaya Sukses Makmur in Jakarta.The method used is explanatory research with analysis techniques using statistical analysis with regression testing, correlation, determination, and hypothesis testing. The results of this study, competence has a significant effect on employee performance by 40.4%; the hypothesis test is obtained t count> t table or (6.792> 1.995). Career development significantly affects employee performance by 42.0%; hypothesis testing is obtained t count> t table or (7.017> 1.995). Competence and career development simultaneously affect employee performance substantially with the regression equation Y = 9.136 + 0.371X1 + 0.405X2, and the contribution of the effect is 54.7%, hypothesis testing is obtained F count> F table or (40.497> 2.740).